Molecular identification of viral agents associated with acute conjunctivitis: a prospective controlled study - Akçay, Emine; Çarhan, Ahmet; Hondur, Gözde; Tufan, Zeliha Koçak; Duru, Necati; Kılıç, Selçuk; Ensari, Ezgi Naz; Uğurlu, Nagihan; Çağıl, Nurullah (The Brazilian journal of infectious diseases, 2017)
Viral conjunctivitis are the most frequent infections in ophthalmology clinics. The diagnosis is usually relying on clinical findings and medical history. However, topical antibiotics are often used unnecessarily addition to symptomatic treatment because of unsure agents. We aimed to detect the Adenovirus, Coxsackievirus and Enterovirus from conjunctiva and pharyngeal samples of patients. The conjunctiva and pharyngeal samples of the patients with conjunctivitis were taken by Virocult transport media and kept at −80̊C up to study day. Adenovirus spp, Enterovirus 70 and Enterovirus 71, Coxsackie A24 and Coxsackie A16 were detected by real-time PCR. Samples from healthy health care workers of ophthalmology clinic were used for control group. A total of 176 samples (conjunctival and pharyngeal samples of 62 patient and 26 healthy subjects) were included. The mean age of 34 (55.7%) male and 27 (44.3%) female patients was 34±17. Twenty five (40.3%) of the patients were receiving antibiotic drops at first visit. The main etiologic agent in conjunctival samples was found to be Adenovirus (46/62, 74.2%) followed by Enterovirus 70 (4/62, 6.4%) and Enterovirus 71 (4/62, 6.4%). Coxsackievirus 16 and 24 were also found in 2 patients (1/62 each, 1.6%). Pharyngeal samples were also positive for Adenovirus (20/62, 32.3%), Enterovirus 70 and 71 (7/62, 11.3% and 5/62, 8.1% respectively), Coxsackievirus 16 and 24 (2/62, 3.2% and 1/61, 1.6%). It is very difficult in viral conjunctivitis to make clinical differentiation caused by different agents because of common clinical signs and symptoms. In routine clinical work, the viral conjunctivitis usually related with Adenovirus. But almost one fourth of the patients’ conjunctivitis were not related to Adenovirus, which shows the importance of the laboratory diagnostics. True diagnosis plays an important role on prevention of contamination and unnecessary use of antibiotics in viral conjunctivitis.